Anisotropic freeze-cast collagen scaffolds for tissue regeneration: How processing conditions affect structure and properties in the dry and fully hydrated states. (February 2019) - Divakar, Prajan; Yin, Kaiyang; Wegst, Ulrike G.K.
Abstract: Few systematic structure–property-processing correlations for directionally freeze-cast biopolymer scaffolds are reported. Such correlations are critical to enable scaffold design with attractive structural and mechanical cues in vivo. This study focuses on freeze-cast collagen scaffolds with three different applied cooling rates (10, 1, and 0.1 °C/min) and two freezing directions (longitudinal and radial). A semi-automated approach for the structural characterization of fully hydrated scaffolds by confocal microscopy is developed to facilitate an objective quantification and comparison of structural features. Additionally, scanning electron microscopy and compression testing are performed longitudinally and transversely. Structural and mechanical properties are determined on dry and fully hydrated scaffolds. Longitudinally frozen scaffolds have aligned and regular pores while those in radially frozen ones exhibit greater variations in pore geometry and alignment. Lamellar spacing, pore area, and cell wall thickness increase with decreasing cooling rate: in longitudinally frozen scaffolds from 25 µm to 83.5 µm, from 814 µm 2 to 8452 µm 2, and from 4.21 µm to 10.4 µm, and in radially frozen ones, from 69 µm to 116 µm, from 7679 µm 2 to 25, 670 µm 2, and from 6.18 µm to 13.6 µm, respectively. Both longitudinally and radially frozen scaffolds possess higher mechanical property values, when loaded parallel rather than perpendicular to the ice-crystal growth direction. Modulus and yield strength range from 779 kPa to 4700 kPa and from 38 kPa to 137 kPa, respectively, as a function of cooling rate and freezing direction. Collated, the correlations obtained in this study enable the custom-design of freeze-cast collagen scaffolds, which are ideally suited for a large variety of tissue regeneration applications. Graphical abstract: